Observing traumatic events: Indirect effects of flood shocks on well-being and preferences - Wiebke Stein; Reinhard A. Weisser (Leibniz Universität Hannover, Wirtschaftswissenschaftliche Fakultät, 2020)
This paper investigates how witnessing adverse weather events affects individuals' perceptions and consequently their personal well-being. To identify potential exposure to a weather shock, we link satellite-based data on flooding to an extensive household panel survey from rural Southeast Asia. We find that mere proximity to a potentially adverse shock, even without reporting any actual experience of the shock, can be sufficient to reduce individual well-being levels. This effect is not only restricted to the present but can also impinge on expected future well-being dynamics. Such a persistent distortionary effect from witnessing a weather shock may also have politico-economic repercussions by, for instance, altering support for redistributive policies.
Keywords: I31; Q51; R23; 330; Environmental shocks; Perception; Subjective well-being; GIS data; MODIS flood mapping